Parody, Intertextuality and Subversion of Gender Stereotypes in Angélica Gorodischer's Science Fiction (Castilla. Estudios de Literatura, 2019)
Great part of Angelica Gorodischer's narrative belongs to Fantasy and Science Fiction literature. For instance, Opus Dos (1967), Kalpa Imperial (1983/84) and Trafalgar (1979), contribute to the development of Science Fiction in Argentine since the 1960s. Gorodischer's Science Fiction is always unorthodox, hybrid and is joined with Fantastic Literature and Speculative Fiction. The reflection on Latin America and Argentina through topics of Science Fiction is the main feature. Criticisms of imperialism, ethnocentrism and androcentricity permeate Gorodischers’ works. This work aims to establish the main features of Gorodischer's Science Fiction. For instance, those features that imply the postmodernization of this genre and the subversion of gender stereotypes in canonic Science Fiction.